2020
DOI: 10.3390/nu12123832
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Omega-3 Long-Chain Polyunsaturated Fatty Acids Are Associated with Bone Metastasis Formation in Premenopausal Women with Breast Cancer: A Retrospective Study

Abstract: In the present study, we investigated various biochemical, clinical, and histological factors associated with bone metastases in a large cohort of pre- and postmenopausal women with breast cancer. Two hundred and sixty-one consecutive women with breast cancer were included in this study. Breast adipose tissue specimens were collected during surgery. After having established the fatty acid profile of breast adipose tissue by gas chromatography, we determined whether there were differences associated with the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In recent years, preclinical [ 17 , 18 , 19 ] and clinical studies [ 20 , 21 ] have shown that omega-3 polyunsaturated fatty acids (ω-3 PUFA) represent an efficient, supportive therapeutic approach for the treatment of breast cancer [ 22 ]. They are considered essential dietary nutrients considering that they cannot be produced naturally through biochemical and metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, preclinical [ 17 , 18 , 19 ] and clinical studies [ 20 , 21 ] have shown that omega-3 polyunsaturated fatty acids (ω-3 PUFA) represent an efficient, supportive therapeutic approach for the treatment of breast cancer [ 22 ]. They are considered essential dietary nutrients considering that they cannot be produced naturally through biochemical and metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“… Peak No. List of compounds Peak area (%) Retention time Reported Anticancer activity 1 2-Pentanol 3.28 4.321 2 4-methyl-3-pentanol 6.90 6.37 3 2-nonanone 0.12 9.78 4 Hexadecanoic acid 4.05 22.89 5 9,12-Octadecanoic acid 1.82 6.76 24.54 25.19 ( Goupille et al, 2020 ) 6 9,12,15- Octadecatrienoic acid 3.11 24.59 ( Zhang et al, 2020 ) 7 Cyclotrisiloxane 0.12 0.67 0.49 0.43 0.89 1.08 1.01 28.68 30.28 30.64 30.73 31.06 31.51 34.32 ( Bouabdallah et al, 2016 ) 8 Eicosane 3.38 2.98 29.43 30.826 ( Ignatenko et al, 2006 ) 9 13-Decosenamide 8.16 30.096 10 Cyclohexane 2.55 32.36 11 Alpha-tocopherol 1.94 32.78 ( Jiang, 2019 ) 12 Campesterol 3.19 33.85 ( Alvarez-Sala et al, 2019 ) 13 Stigmasterol 7.85 34.21 ( Alvarez-Sala et al, 2019 ) ...…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found that the two major omega-3 EPA and DHA at 60 µM had no obvious effect on the growth and proliferation of NSCLC cells, but effectively inhibited the migration and invasion of lung cancer cells, whereby the inhibitory effect of DHA was more pronounced that of EPA. Recently, Goupille et al [ 24 ] reported that the levels of omega-3 in breast adipose tissue were negatively correlated with the development of bone metastases in premenopausal women with breast cancer. Pfister et al [ 25 ] found that omega-3 suppresses the invasion in colorectal cancer cells by a PI3K-dependent mechanism but had no effect on cell proliferation.…”
Section: Discussionmentioning
confidence: 99%